The Values of Dakwah in the Film Siksa Neraka as a Means to Enhance Public Spiritual Awareness - Putri Aulia Andita; Ahmad Tamrin Sikumbang (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Film is an audiovisual communication medium that not only provides entertainment but also conveys information and resonates emotionally with its audience. Additionally, film is part of mass communication media and is often used as a medium to depict the social life of a community. As one of the characteristics of mass media, film is one of the most effective communication tools. Essentially, film screenings are used in media studies as a means to deliver social, cultural, and other messages. The purpose of this research is to clarify the values of dakwah as messages contained in the film Siksa Neraka directed by Anggi Umbara. The approach used in this research is a qualitative approach with a descriptive method. The data used in this research consist of documents in the form of video files of the film Siksa Neraka and data from various sources relevant to the study. The subject of this research is the film titled Siksa Neraka, directed by Anggi Umbara. This study investigates the dakwah values contained in scenes from the film. The subject of the study is the scenes in the film Siksa Neraka that contain dakwah values in the form of messages related to creed (aqidah), Islamic law (sharia), morality (akhlaq), and worship (muamalah). Based on the findings, there are 57 scenes in the film Siksa Neraka, but not all of them contain messages with dakwah values. The dakwah values as messages in the film Siksa Neraka are found in 34 messages spread across 57 scenes. There are 9 messages on aqidah, 12 messages on sharia, 3 messages on muamalah worship, and 10 messages on akhlaq.